EFFECT OF ANTANAN (CENTELLA ASIATICA) AND VITAMIN C ON THE BURSA OF FABRICIUS, LIVER MALONALDEHIDE AND PERFORMANCE OF HEAT-STRESSED BROILERS - TOHA SUTARDI; ENGKUS KUSNADI; REVIANY WlDJAJAKUSUMA (BIOTROPIA, 2005)
High environmental temperatures may cause heat stress  in poultry. This may increase water consumption, decrease feed consumption and in rum, decrease productivity level. In addition, high temperature contributes to oxidative stress, a condition where oxidant activity (free radicals) exceeds antioxidant activity. In our research, antanan (Centelta asiatica)  and vitamin C were utilized as anti heat-stress agents for heat-stressed broilers. We used 120 male broilers 2 - 6  weeks old, kept at 31.98 ± 1.94 °C during the day and 27.36 ± 1.31 °C at night. The data collected were analyzed with a completely randomized factorial design of  2 x 3 (2 levels of vitamin C, 3 levels of antanan at 4 replications) and continued with the contrast-orthogonal test when significantly different. The results indicate that the treatments of 5 and 10% of antanan with or without 500 ppm of vitamin C and vitamin C alone significantly (P